A homozygous mutation p.Arg2167Trp in FREM2 causes isolated cryptophthalmos. (24th April 2018) - Yu, Qian; Lin, Bingying; Xie, Shangqian; Gao, Song; Li, Wei; Liu, Yizhi; Wang, Hongwei; Huang, Danping; Xie, Zhi
Abstract: Cryptophthalmos (CO, MIM: 123570) is rare congenital anomalies of eyelid formation, which can occur alone or in combination with multiple congenital anomalies as part of Fraser syndrome (FS) or Manitoba Oculotrichoanal syndrome. Causal mutations have been identified for these syndromes but not in the isolated cases. Here, we described two patients from two unrelated Chinese families: one with unilateral isolated CO, while the other with unilateral CO and renal agenesis. A novel homozygous mutation (c.6499C>T: p.Arg2167Trp) and compound heterozygote mutations (c.15delG; c.6499C>T: p.Arg2167Trp) in FREM2 (NM_172862) were identified for the two patients, respectively. The deletion mutation c.15delG resulted in a frameshift and triggered the nonsense-mediated mRNA decay. For the shared missense mutation, p.Arg2167Trp altered a conserved residue and was predicted to affect protein structure by in silico analysis. Functional analysis revealed that Arg2167Trp mutant decreased its interaction with FRAS1 related extracellular matrix 1 (FREM1) and impaired the function of the FRAS1–FRAS1 related extracellular matrix 1 (FREM2)–FREM1 ternary complex required for normal embryogenesis. Furthermore, considering that mutation (c.5914C>T: p.Glu1972Lys) in FREM2 causes FS, a severe systemic disorder, we also compared these two different missense mutations. Our results showed that p.Arg2167Trp had a weaker effect in interrupting interactions between FREM2 and FREM1 than FS-associated missense mutation p.Glu1972Lys. Overall, our data demonstrate that the homozygous mutation p.Arg2167Trp in FREM2 causes isolated CO, which will facilitate our better understanding of the molecular mechanisms underlying the disease.